Potensi dan Masalah dalam Pengembangan Ekonomi Lokal di Kampung Tematik Jahe Merah, Kelurahan Jatirejo, Kota Semarang - Naibaho, Theresia Amadis H. (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
Kampung Tematik Jahe Merah (Kajera) is one of the thematic villages in Jatirejo Village, Gunungpati District, Semarang City. The development of the thematic village is one of the efforts to develop the local economy of the area. This study aims to identify the potential problems of thematic village development. This research uses SWOT analysis method to identify the strengths, weaknesses, opportunities, and threats faced in the management of thematic village. Data collection was conducted through primary data obtained from observations and interviews, and secondary data through document processing. The results showed that there are still obstacles such as crop failure and lack of product innovation in the following Kampung Tematik Jahe Merah management activities. Therefore, effective marketing strategies and community empowerment are needed to create product diversification and increase the capacity of village managers. Thus, the development of the Kampung Tematik Jahe Merah can contribute to the development of the local economy in Jatirejo Village and achieve economic resilience that is able to increase the income and quality of life of local communities.Â